Mitigation of Non-linear Distortion Using PTS and IDAR Method for Multi-Level QAM-OFDM System - Pisit Boonsrimuang; Pornpawit Boonsrimuang; Kazuo Mori; Tawil Paungma; Hideo Kobayashi (My University, 1970)
The future satellite communication systems are required to support the higher transmission data rate for providing the multimedia services by employing the efficient modulation method such as multi-level QAM. The employment of single carrier transmission with multi-level QAM would cause the fatal degradation of signal quality due to the non-linear amplifiers located at the earth station and satellite. To overcome this problem, we have proposed the multilevel QAM-OFDM technique with IDAR (Improved Decision Aided Reconstruction) method designed for non-linear satellite channel. However, the proposed method could not mitigate the non-linear distortion sufficiently when modulation level becomes higher such as 64QAM. This paper proposes the combined scheme of partial transmission sequence (PTS) and OFDM-IDAR methods so as to enable the usage of higher multi-level QAM method, which can achieve the higher transmission data rate with keeping the better bit error rate performance in the non-linear satellite channel. The various computer simulations are conducted in this paper to verify the effectiveness of proposed method in the non-linear satellite channel.
Keywords: QAM; Communications satellite; Distortion (music); Modulation (music); Satellite Communication Systems